The comprehensive Africa agriculture development programme as a collective institution - Kolavalli, Shashidhara; Birner, Regina (International Food Policy Research Institute, 2013)
The Comprehensive Africa Agriculture Development Programme (CAADP) was designed to promote the transformation of agriculture in SSA. Under this program, African countries have committed to seek development through agriculture led growth by targeting at least 6 percent growth and by allocating about 10 percent of government budget to the sector. In return, the donor community has implicitly committed to increase their support to agriculture using the CAADP mechanism, while at the same time coordinating their activities in this sector and aligning them with the CAADP priorities set by the African countries themselves.